2004
DOI: 10.1124/jpet.104.070060
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Activates Nuclear Factor of Activated T Cells c2 (NFATc2) and Prevents Cell Cycle Entry in T Cells

Abstract: We used primary peripheral blood T cells, a population that exists in G 0 and can be stimulated to enter the cell cycle synchronously, to define more precisely the effects of nicotine on pathways that control cell cycle entry and progression. Our data show that nicotine decreased the ability of T cells to transit through the G 0 /G 1 boundary (acquire competence) and respond to progression signals. These effects were due to nuclear factor of activated T cells c2 (NFATc2)-dependent repression of cyclin-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The functional significance of this finding was confirmed in the Nfatc2-deficient mice that had enhanced CDK4 expression and activity restricted to the peripheral T cell pool, which shows dysregulated expansion in these animals (43,44). An important finding from this work was that the association of Nfatc2 with AP-1 transcription factors was a critical determinant of its activity as a transcriptional activator or a transcriptional repressor.…”
Section: Nfatc2 In Negative Regulation and Survivalmentioning
confidence: 77%
See 1 more Smart Citation
“…The functional significance of this finding was confirmed in the Nfatc2-deficient mice that had enhanced CDK4 expression and activity restricted to the peripheral T cell pool, which shows dysregulated expansion in these animals (43,44). An important finding from this work was that the association of Nfatc2 with AP-1 transcription factors was a critical determinant of its activity as a transcriptional activator or a transcriptional repressor.…”
Section: Nfatc2 In Negative Regulation and Survivalmentioning
confidence: 77%
“…It is now apparent that survival and quiescence are actively enforced in T cells (41)(42)(43)(44)(45)(46)(47). This paradigm has long been operative in other systems where survival requires signals from a substrate or matrix (avoidance of anoikis) (48,49) and where quiescence is enforced by signals delivered when cells contact each other (50).…”
Section: Intrinsic Negative Regulators Of T Cell Activationmentioning
confidence: 99%
“…Among >160 genes in HSA 7p, diacylglycerol kinase-h and histone deacetylase-9 are two potentially ''novel'' tumor suppressor genes (43,44). In the context of chromosome gains seen in canine T-cell lymphomas, candidates that may encode ''novel'' oncogenes include interleukin-15, FK506 binding protein-7, and histone acetyltransferase-1, which map to HSA 4q31, 2q31.3, and 2q31.2-33.1, respectively, and could initiate autocrine growth loops (45,46), lower total calcineurin and NFATc2 activity (47), or counteract the activity of histone deacetylase (48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is documented that chronic exposure to cigarette compounds such as nicotine suppresses immune functions including T-cell proliferation. 33,34 A study by Frazer-Abel et al 15 showed that direct addition of nicotine to T cells in vitro decreases their proliferation by prevention of cell-cycle entry in G 0 -G 1 transition. However, the present results imply that smoking exerts differential effects in patients leading to altered T-cell proliferation and that these effects are disease associated rather than related to smoking as no proliferative difference was observed between healthy smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Nicotine, the major active chemical in cigarettes, has been shown to impair antigen-driven T-cell response and inhibit proliferation in rodents as well as humans. [13][14][15][16] T lymphocytes have integral function in cell-mediated immunity and are involved in host defence against infectious agents. Peripheral changes in the immune system of schizophrenia patients, such as decreased cellular immune response 17,18 and altered cytokineexpression, 19 have been reported.…”
Section: Introductionmentioning
confidence: 99%